2015
DOI: 10.3109/09638237.2015.1036968
|View full text |Cite
|
Sign up to set email alerts
|

Acute mental health service use by patients with severe mental illness after discharge to primary care in South London

Abstract: The majority of the discharged patients were re-referred to mental health services. Although these were more stable, there was no difference from the transferred group on acute service use. Further support may be required in primary care to maintain stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…Within mental healthcare, a refocusing of resources under the Measure certainly appears to have been achieved through prioritising those with the most serious mental illness to receive expensive secondary care, whilst discharging others to primary care. This overall strategy, in its particular manifestation in the form of the Measure, may be related to a narrow, neoliberalist interpretation of person-centred recovery (Ramanuj et al, 2015). Here, the aim is to increase autonomy and responsibility for people with mental illness, coupled with reduced service dependency (Lester & Gask, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Within mental healthcare, a refocusing of resources under the Measure certainly appears to have been achieved through prioritising those with the most serious mental illness to receive expensive secondary care, whilst discharging others to primary care. This overall strategy, in its particular manifestation in the form of the Measure, may be related to a narrow, neoliberalist interpretation of person-centred recovery (Ramanuj et al, 2015). Here, the aim is to increase autonomy and responsibility for people with mental illness, coupled with reduced service dependency (Lester & Gask, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a long debate about who should be referred to specialist mental services or who should receive care in a primary care setting and how the interface should be most efficiently configured to promote joint working between professionals (Gask, Lester, Kendrick, & Peveler, ; Lester, Tritter, & Sorohan, ). However, there are noted deficiencies in the primary care for these patients and a call for more support in primary care services (NHS England ; Ramanuj et al., ; Reilly et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in south London highlighted difficulties facing increased primary care for people with SMI (Ramanuj et al, 2015). This study showed that 58.2% of people discharged from secondary to primary care were referred back to secondary care within two years of their original discharge (Ramanuj et al, 2015).…”
Section: The Study Context and Backgroundmentioning
confidence: 99%
“…More recently, it has been argued that primary care is now sufficiently mature as a discipline to take on a lead role in mental health service delivery (Currid et al, 2012;Green and Thoroughgood, 1998;Lester et al, 2004;WHO, 2008). An increased emphasis on primary mental healthcare delivery may also be related to a recovery approach aimed at reducing specialist service dependency and service provision (Lester and Gask, 2006;Ramanuj et al, 2015). Another key driver behind this transition is the notion that primary care is more cost-effective than secondary or hospitalised care (Ramanuj et al, 2015;van Dijk et al, 2014).…”
Section: The Study Context and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation